Reviewing the extent of rural and remote considerations in elder abuse policy: A scoping review. (19th August 2019) - Blundell, Barbara; Warren, Amy
Abstract: Objective: To identify national and international research and literature focussed on policy responses to elder abuse in rural and remote communities to generate recommendations for Australian responses. Design: Scoping literature review. Setting: Australia (some international policy also included). Participants: National and international elder abuse policy documents relating to rural and remote responses were reviewed. Seventy‐two stakeholders were invited to contribute literature that may have been missed in the scoping review. Main outcome measure(s): Identification of the extent to which issues for rural and remote communities were discussed in elder abuse policy. Result: Of the 13 Australian policy documents reviewed, only four made mention of rural and remote communities, though this was generally only in regard to increase in vulnerability. No mention of these communities were identified in reviewed global policy. One document focussing on abuse in rural and remote Indigenous communities highlighted the importance of developing culturally appropriate responses hinged on community collaboration and consultation. Conclusion: Consideration of rural and remote communities in elder abuse policy is generally not meaningful. It is recommended that future policy development includes recognition of the distinct features of elder abuse in rural and remote communities, as well as how these features may impact on prevention and responses in these locations. These features include geographical isolation, lack of access to services and transportation, confidentiality and privacy issues, and the need for culturally sensitive approaches to address elder abuse for Indigenous people which take into account the impact of historical disenfranchisement.